Phenolic Ecotoxins in River Water: Survey on Knowledge and Practices of Road-Side Food Vendors Operating Along River Chania Bank Fringes in Thika Sub- County, Kenya - Muitta, Esther (Natural Science Journal, 2024)
Purpose: Phenolic ecotoxins consumed in raw surface water from river sources has been implicated in causing diseases of high burden such as cancers, in Kenya. This study was conducted in Thika Sub County, and data collected from roadside food vendors and food hawkers who operate small scale street food business along the fringes and banks of River Chania. The study’s objective was to establish the knowledge on Phenolic ecotoxins present in river water and practices of the study respondents. Methodology: A crossectional descriptive study design was used, in which combined interviews and questionnaire enquiries conducted from, n=341, small-scale road side food vendors and hawkers was analyzed. Findings: Data reveals that none of the respondents had knowledge on Phenolic ecotoxin contaminants and additionally a strongly associated correlation (P<0.001, χ222.6 and df 1), further augments the disclosure that, poor knowledge of raw river water safety and hygiene does result to body harm and ill health. Unique Contribution to Theory, Policy and Practice: There is increased need and effort to scale up the sensitization and awareness on exposure to harmful ecotoxin contaminants from the use of raw river water. Water decontamination mobile units should be considered and introduced especially in urban areas of high population density, transversed by rivers.